Transesterificação de ésteres etílicos e estudo cinético usando a sílica CTA-MCM-41 - Paula, Luana do Nascimento Rocha de (Universidade Federal de São Carlos, 2020)
The synthesis of biodiesel, through transesterification, occurs industrially in the presence of basic homogeneous catalysts, where others steps are necessary, such as washing and neutralization of the final product due to the difficulty in separating the catalyst, which does not occur in heterogeneous routes. In this sense, the use of mesoporous hybrid silicas containing organic cations, as heterogeneous catalysts, is very effective in the transesterification reaction, since the presence of siloxide sites (≡SiO-) increases their catalytic activity. Therefore, the objective of this work was the synthesis of basic silicas and their subsequent application in the transesterification of different ethyl esters, as model reactions, in order to verify the influence of the size of the ester chain in the reaction in addition to the adjustment of kinetic models and determining the parameters of each reaction. The catalysts were synthesized using the classic synthesis of CTA-MCM-41 and also with the 2-ethylhexyl acrylate monomer, in a monomer / surfactant ratio equal to 0.2 and with the post-synthesis irradiation method. The kinetic models were adjusted to the reactions using only CTA-MCM-41 as a catalyst. By X-ray diffractometry (XRD) it was possible to verify the formation of the hexagonal structure of the silicas and the expansion of the irradiated silica channel. Scanning electron microscopy (SEM) and transmission electron microscopy showed that the catalysts do not differ in morphology and that they have cylindrical tubes ordered in a single direction. In addition, thermogravimetry (TG), spectroscopy in the infrared region (FTIR-ATR) and elementary analysis (CHN), confirmed the presence of the monomer in the irradiated silica. It was also found that the increase in the size of the ester chain of the model reactions implies a reduction in catalytic activity, probably due to both inductive effects and diffusion restrictions with the increase in the size of the carbon chain. The pseudo-first order model showed better adjustment to the reaction kinetics, and activation energies were obtained for each of the reactions, which varied between 41.29-48.30 kJ / mol as the carbon chain (acetate-pentanoate). These values were found to be within the range of the literature for transesterification of monoesters using basic heterogeneous catalysts.
Transesterification of ethyl esters and kinetic study using CTA-MCM-41 silica
Keywords: CTA-MCM-41; Transesterificação; Ésteres etílicos; Modelagem cinética; Transesterification; Ethyl esters; Kinetic modeling; ENGENHARIAS::ENGENHARIA QUIMICA::TECNOLOGIA QUIMICA; ENGENHARIAS::ENGENHARIA QUIMICA